A glimpse at Hilbert space operators : Paul R. Halmos in memoriam - Axler, Sheldon Jay; Rosenthal, Peter; Sarason, Donald (Operator theory, advances and applications, 2010)
This volume is a memorial to Paul R. Halmos by operator theorists he inspired. It contains expository articles by prominent operator theorists, photos of Paul and taken by Paul, and three tributes to Paul written shortly after his death in 2006. From the expository articles, this generation of operator theorists and future generations will get a glimpse of many aspects of their subject, and of how Paul enriched and advanced it through his fundamental insights and prescient questions. --